CLINICAL AND TOMOGRAPHIC FINDINGS IN A RAM WITH SIGNS OF NERVOUS DISORDERS: A CASE REPORT - Sandoval M., Rocío (2014)
This report describes the clinical and computed tomography findings in a stud Corriedale ram, 3.5 years old, with signs of nervous disorders. Physical examination showed signs of depression, abnormal posture, ataxia, right facial paresis, due to a left hemisphere syndrome. X-ray examination revealed no abnormalities, but a cranial computed tomography scan showed a hypodense bilobed mass of 6.4 x 3.4 cm anteroposterior by transverse diameters, located from the front to the occipital region of the left side. The residual parenchyma was shifted towards the periphery with alteration of the density, unable to differentiate the gray matter from the white matter, the ventricular cavities were collapsed, the posterior fossa showed a depression exerted by the cerebellar lesion, and the epidural and subdural spaces were diminished. The pathological diagnosis was hypodense tumoral lesion in the left cerebral hemisphere crossing the midline with signs of intracranial hypertension compatible with glioblastoma.